The Enfield Poltergeist Tapes: One of the Most Disturbing Cases in History. What really happened? by Melwyn J. Willin - Nahm, Michael (Journal of Scientific Exploration, 2019)
The present book provides valuable background information on a controversial poltergeist case that was investigated by members of the Society for Psychical Research (SPR) from the end of 1977 to summer 1979. One of its chief investigators, Guy Lyon Playfair (1935-2018), publicized the Enfield case in a remarkable book about the reported phenomena in 1980, a second and third edition followed in 2007 and 2011. Whilst Playfair always admitted that some of the phenomena were staged by the children living in the house, he held the general opinion that the gross majority of the phenomena including the peculiar voices the children spoke with represented genuine poltergeist disturbances. Nevertheless, several other visitors to the Enfield house were much more pessimistic and believed that most likely, all phenomena were staged. Willin’s book plunges straight into the controversies and quarrels that members of the SPR engaged during the investigation of the case. In this context, he presents excerpts from previously unpublished material. The most peculiar source is the collection of the hundreds of hours of tape recordings taken by Maurice Grosse, the second chief investigator of the case. Willin listened to all of them and provided a summary of their contents and most interesting sections. He also presented excerpts from a previously unpublished report written by members of the SPR’s “Enfield Poltergeist Investigation Committee” (EPIC) that contains numerous witness testimonies. Furthermore, he asked several people involved in the case to comment on their experiences from today’s perspective, and included the received responses in his book as well. In addition, Willin compared the phenomenology of the Enfield case with similar occurrences reported from the “Mount Rainier Case”.